2013
DOI: 10.1016/j.cemconcomp.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the global warming impact of bridge rehabilitations by using Ultra High Performance Fibre Reinforced Concretes

Abstract: a b s t r a c tUltra-High Performance Fibre Reinforced Concrete (UHPFRC) is charact erized by a unique combination of extremely low permeability, high strength and deformability. Extensive R&D works and applications over the last 10 years have demonstrated that cast on site UHPFRC is a fast, efficient and price competitive method for the repair/re habilitation of existing structures. More recently, an original concept of ECO-UHPFRC with a high dosage of mineral addition, a low clinker content, and a majority o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(65 citation statements)
references
References 30 publications
0
42
0
5
Order By: Relevance
“…As commonly known, the cement production is said to represent about 7% of the total anthropogenic CO 2 emissions [15][16][17]. Hence, one of the key sustainability challenges for the next decades is to design and produce concrete with less clinker and inducing lower CO 2 emissions than traditional ones, while providing the same reliability, with a much better durability.…”
Section: Introductionmentioning
confidence: 99%
“…As commonly known, the cement production is said to represent about 7% of the total anthropogenic CO 2 emissions [15][16][17]. Hence, one of the key sustainability challenges for the next decades is to design and produce concrete with less clinker and inducing lower CO 2 emissions than traditional ones, while providing the same reliability, with a much better durability.…”
Section: Introductionmentioning
confidence: 99%
“…fly ash (FA), ground granulated blast-furnace (GGBS), limestone powder (LP) and silica fume (SF)) are given directly, without any detailed explanations or theoretical support. Moreover, due to the complex cementitious system of UHPC (extremely low water amount and relatively high SP content), the influence of different mineral admixtures on the hydration kinetics and properties of UHPC still needs further clarification [6][7][8][11][12][13][14][15]. As commonly known, GGBS has hydraulic properties although the rate of the reaction with water is low [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the quickly developing construction industry, concrete expect the compressive strength is also required to have high flexural strength, workability and durability, which resulted the development of Ultra-High Performance Concrete (UHPC) and Ultra-High Performance Fibre Reinforced Concrete (UHPFRC) [6][7][8]. Nevertheless, as the sustainable development is currently a pressing global issue and various industries have strived to achieve energy savings, the high material cost, high energy consumption and CO 2 emission for UHPC are the typical disadvantages that restrict its wider application [9][10][11]. Hence, how to efficiently produce UHPC, based on materials point of view, still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…The cement in UHPC becomes comparable to the coarse aggregates used in conventional concrete making it very costly and unsustainable [2]. It is reported that the production of cement alone contributes about 7% of CO2 emissions, which impacts on global warming [3]- [5]. In line of making the world greener, the recent direction in concrete industry is to produce sustainable concrete with lower CO 2 emissions while providing same reliability with an improved durability.…”
Section: Introductionmentioning
confidence: 99%
“…Cement content in UHPC can reach as high as 800-1000 kg/m3 compared to 300-500 kg/m 3 for conventional concrete [2], [5]. Using certain amount of cement replacement material in UHPC would lower the amount of cement used in the mix that leads to a lower cost of UHPC.…”
Section: Introductionmentioning
confidence: 99%